2006
DOI: 10.1303/aez.2006.507
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone of the soybean pod borer, Leguminivora glycinivorella (Lepidoptera: Tortricidae): Identification and field evaluation

Abstract: With reference to the data of synthetic standards, GC-EAD and GC-MS analyses of a pheromone gland extract of the soybean pod borer, Leguminivora glycinivorella (Lepidoptera: Tortricidae), resulted in three acetates [dodecyl acetate, (8E,10E)-8,10-dodecadienyl acetate (E8,E10-12:OAc), and its (8E,10Z)-isomer] at a ratio of 10 : 100 : 2.5 as a candidate of the pheromone. While the contents in the glands were low and even the titer of the major pheromonal component was ca. 0.5 ng/female, the positions of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Of note, some long-chained 2Z,4E-configured dienes have been found in nature, mostly as pheromones or as part of more complex natural products, such as product 6 a or a compound related to product 6 g. [9] Accordingly, applications of this new method in natural product synthesis can be envisaged.…”
mentioning
confidence: 99%
“…Of note, some long-chained 2Z,4E-configured dienes have been found in nature, mostly as pheromones or as part of more complex natural products, such as product 6 a or a compound related to product 6 g. [9] Accordingly, applications of this new method in natural product synthesis can be envisaged.…”
mentioning
confidence: 99%
“…The effect on catch when other synthetic compounds were combined with EE -8,10-12:Ac varied with the compound and dose. In 2006, it has been reported that E- 8-12:Ac strongly inhibited the attractiveness of EE- 8,10-12:Ac to L. glycinivorella in Japan [ 1 ]. When tested as a single compound, E -8-12:Ac was not attractive to L. glycinivorella males ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 12:Ac has been detected in a gland extract of L. glycinivorella pheromone, and the GC-EAD showed that it was antennally active [ 1 ]. When tested as a single compound, 12:Ac alone was not attractive to L. glycinivorella males ( Table 1 ), and significantly decreased mean catch when added to traps baited with EE- 8,10-12:Ac at doses of 0.01 and 0.5 mg per septum ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the somewhat conservative polices and legal obstacles to transgenic crops in many countries limited the applications of this procedure in soybean [13]. Similarly, certain sex pheromones have also been chemically identified and used to monitor population dynamics and control SPB by mating disruption [14]. The use of resistant cultivars is also an effective way for reducing insect pest damage in combination with other non-chemical control measures [15].…”
Section: Introductionmentioning
confidence: 99%